PENINGKATAN HASIL BELAJAR IPAS MATERI SISTEM PERNAPASAN PADA MANUSIA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SD INPRES SIKUMANA 2 KOTA KUPANG - Elfiana Juninta Hello; Jannes Bastian Selly; Kurniayu Triastuti R.A Ratu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve IPAS learning outcomes on the subject of the humanrespiratory system through a problem based learning model in grade V at SD InpresSikumana 2 in Kupang City. The method used is Classroom Action Research (CAR),which was carried out in two cycles, consisting of the stages of planning,implementation, observation, and reflection. Data collection techniques were carried outthrough obervation of teacher and student activities, as well as learning outcome tests.The subjects of this study were 28 grade students, consisting of 15 boys and 13 girls.The results of the study showed a significant increase in learning outcomes, learningcompleteness increased from 50% in cycle I to 86% in cycle II. Thus, it can beconcluded that the application of the problem based learning model can improve studentlearning outcomes in IPAS learning on the subject of the human respiratory system.